The study of the humerus and femur length as combined predictors of the gestational age of human fetuses using ultrasonography - B. R., Chaithra Rao; Sreepadma, Sunkeswari (International Journal of Research in Medical Sciences, 2017)
Background: Ultrasound dating of pregnancy is the most effective and easiest method presently used to assess the gestational age of fetus. The study evaluates the diaphyseal lengths of humerus and femur as combined parameters to estimate the gestational age of the fetus at the time of examination. Methods: The study was done on 152 pregnant women of gestational age from 15 to 40 weeks attending antenatal clinic of a certain medical college hospital. Subjects with maternal disease known to affect normal fetal growth, history of recurrent miscarriages and of chronic medications, multiple gestations or other complications and major fetal abnormalities were excluded. The diaphyseal lengths of humerus and femur were measured in a standardized manner. The relationship of the humerus and femur length in centimeters is compared with the gestational age in weeks. The multiple correlation equation of humerus and femur length with the gestational age was deduced. Results: It was observed that the diaphyseal length of humerus and femur gradually increased from 15 weeks to 40 weeks of gestation and by applying multiple correlation, a formula was derived to calculate the gestational age. Conclusions: The measurement of the humerus and femur length (in cm) can be an important additional parameter for estimating gestational age along with other parameters and can be used to predict the gestational age of fetuses belonging to that geographical area using the derived formula.